1972
DOI: 10.1001/archinte.1972.00320060091011
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Idiopathic Postural Hypotension

Abstract: The clinical response to a monamine oxidase inhibitor and a sympathomimetic amine or tyramine containing foodstuffs have been studied in four patients with idiopathic postural hypotension. Each was receiving fludrocortisone acetate therapy. One patient has had substantial clinical improvement for over 26 months on the combination and another improved symptomatically for nine months before further neurologic deterioration. One patient with additional chronic polymyositis had little change in symptoms.Another wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…(1970), Lewis et al (1972), andNanda et at. (1976), with or without a monoamine oxidase inhibitor, such as tranylcypromine (Pamate, 10-20 mg tid) or phenelzine (Nardil).…”
Section: Drugs That Enhance Norepinephrine Release and Retard Its Reumentioning
confidence: 99%
“…(1970), Lewis et al (1972), andNanda et at. (1976), with or without a monoamine oxidase inhibitor, such as tranylcypromine (Pamate, 10-20 mg tid) or phenelzine (Nardil).…”
Section: Drugs That Enhance Norepinephrine Release and Retard Its Reumentioning
confidence: 99%
“…In three cases of autonomic insufficiency, i. e., orthostatic hypotension without associated tachycardia, Lewis et al [14] reported benefit of tranylcypramine and hydroxyamphetamine combined with fluorohydrocortisone. Frewin et al [7] reported a single case in which a similar effect was pro duced by tranylcypramine, fluorohydrocortisone, and cheese, presumably on the basis of the tyramine content of the cheese.…”
Section: Sympathomimetic Aminesmentioning
confidence: 99%